UPAYA PEMAHAMAN PENDIDIKAN AGAMA ISLAM PADA ANAK-ANAK MELALUI KEGIATAN MENGAJI SORE DI DESA SELING - Ridwan, Muhammad; Nur Hidayat; Khoiruddin Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The world continues to experience very rapid development, especially in the digital world, but in addition to experiencing positive developments it is also a sharp knife in the negative direction, especially for children and adolescents, they become more preoccupied with things that are not useful than having to do useful things such as learning and reciting the Koran. This study aims to see what are the causes of the decline in children's interest in understanding Islamic religious education, and how efforts to increase understanding of Islam through afternoon recitation activities. This research uses a qualitative approach, with primary and secondary data sources, data collection methods are carried out by observation, interviews, and documentation. The results showed that the decline in children's interest in understanding Islamic religious education was caused by several things: the first is that children have been influenced by gadgets, causing them to be lazy to recite the Koran because they are too cool with social media which makes them forget about time and obligations. The second is the wrong association. They make friends with children who do not recite the Koran which causes them to also be lazy to recite the Koran because they are influenced by their friends. then the third is the lack of supervision from parents. Parents are the most important part in the growth and development of children, parents need to supervise children so that children do not get the wrong association and are not addicted to gadgets. Parents must be role models and must be able to manage and control children. Then the last is, the weak Islamic norms set in the family. The family becomes a madrasa, the first educational institution for children, if the family lacks an understanding of the importance of Islamic Religious Education, children will not be interested in learning religion.